Pauttamum Tamil̲um. - Vēṅkaṭacāmi, Mayilai Cīn̲i., 1900-1980, author. Link
1 online resource (xvi, 152 pages).
Keywords: First published in 1940, Mayilai Seeni Venkatasamy's Buddhism and Tamil was one of the pioneering attempts to trace the history of Buddhism in the Tamil country. With judicious exploitation of archaeological, linguistic, and historical sources, Venkatasamy delineates how Buddhism flourished from the 2nd century BCE to the 13th century CE and traces its residual presence in contemporary Tamil culture. The book challenges the then-prevalent belief that Tamil is synonymous with Saivism and problematises the simplistic understanding that Hinduism had always been the religion of India. Venkatasamy's stylistic and literary analysis of Pali and Tamil texts, his careful study of inscriptions, and his extensive fieldwork identify the role of Buddhism in shaping the language, literature, and ethics of Tamil society.